AID EFFECTIVENESS AND THE PARIS DECLARATION: A MISMATCH BETWEEN OWNERSHIP AND RESULTS‐BASED MANAGEMENT?. (14th February 2013) - Sjöstedt, Martin
SUMMARY Although recent years have witnessed substantial changes in the global aid architecture, less effort has been devoted to investigating the process of implementing those changes. By using the Swedish International Development Cooperation Agency (Sida) as an illustrative and critical case, this article shows how a donor development priority—gender—travels from Stockholm and headquarters to a Paris Declaration‐infused aid practice in three cases with different aid modalities: Tanzania, Zanzibar, and Cambodia. More specifically, the qualitative empirical investigation conducted here shows that the implementation of the new aid architecture puts severe and competing demands on development practitioners. At the core of this tension is the fact that although all donors are supposed to promote partner country ownership, harmonize their efforts with other donors, and align themselves with partner country priorities, results‐based management simultaneously implies not only a focus on continuously measuring and reporting results but also stricter prioritizations on behalf of donor governments. Copyright © 2013 John Wiley & Sons, Ltd.